1999
DOI: 10.1007/s004390051091
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-tectorin involvement in hearing disabilities: one gene - two phenotypes

Abstract: The human alpha-tectorin (TECTA) gene has recently been cloned and proposed to be involved in autosomal dominant non-syndromic hearing impairment (NSHI) in two families linked to the DFNA12 locus. We have studied a Swedish pedigree with autosomal dominant NSHI with possible digenic inheritance of the disease, involving locus DFNA12 in chromosome 11 and locus DFNA2 in chromosome 1. Mutation analysis of the TECTA gene in this family has identified eight nucleotide substitutions indicating that TECTA is highly po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 21 publications
1
62
2
Order By: Relevance
“…An additive effect of mutant alleles at the DFNA12 and DFNA2 loci was proposed to explain the variation in severity of a progressive nonsyndromic hearing loss observed in a Swedish family, wherein each separate locus was associated with a mild and sometimes undiagnosed phenotype, but both loci together were associated with a more severe phenotype (Balciuniene et al, 1998). Subsequently, mutations of the alpha tectorin gene TECTA were shown to underlie DFNA12 in this family, but no mutations were found in the gap junction gene GJB3 or the potassium channel gene KCNQ4, which were shown to be responsible for deafness at the DFNA2 locus in other families (Balciuniene et al, 1999). These results do not rule out digenic inheritance, because the DFNA2 locus may include an additional, as yet unidentified, gene that modulates the hearing loss associated with TECTA mutations.…”
Section: Digenic Inheritance and Hearing Loss In Mice And Humansmentioning
confidence: 78%
“…An additive effect of mutant alleles at the DFNA12 and DFNA2 loci was proposed to explain the variation in severity of a progressive nonsyndromic hearing loss observed in a Swedish family, wherein each separate locus was associated with a mild and sometimes undiagnosed phenotype, but both loci together were associated with a more severe phenotype (Balciuniene et al, 1998). Subsequently, mutations of the alpha tectorin gene TECTA were shown to underlie DFNA12 in this family, but no mutations were found in the gap junction gene GJB3 or the potassium channel gene KCNQ4, which were shown to be responsible for deafness at the DFNA2 locus in other families (Balciuniene et al, 1999). These results do not rule out digenic inheritance, because the DFNA2 locus may include an additional, as yet unidentified, gene that modulates the hearing loss associated with TECTA mutations.…”
Section: Digenic Inheritance and Hearing Loss In Mice And Humansmentioning
confidence: 78%
“…Differences in phenotype among DFNA8/12 families appear to be related to the position of the mutations in either the ZP or the ZA domain of a-tectorin as well as the nature of the amino acid substitution (Table 1). Mutations in the ZP and ZA domains have been related to mid-and high-frequency hearing impairment, respectively Verhoeven et al 1998;Govaerts et al 1998;Iwasaki et al 2002;Alloisio et al 1999;Balciuniene et al 1999;Pfister et al 2004;Moreno Pelayo et al 2001). Substitutions replacing cysteines have been implicated in progressive hearing impairment (Alloisio et al 1999;Balciuniene et al 1999;Pfister et al 2004;Moreno Pelayo et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations affecting the ZP domain are associated with midfrequency hearing impairment, whereas mutations in the ZA domain are associated with hearing impairment primarily affecting the high frequencies (Table 1) Verhoeven et al 1998;Govaerts et al 1998;Iwasaki et al 2002;Alloisio et al 1999;Balciuniene et al 1999;Pfister et al 2004;Moreno Pelayo et al 2001). Hearing impairment can range from mild to severe and has prelingual or postlingual onset.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Mutations in the TECTA gene have Genetic causes of NSHL in Iran N Mahdieh et al been found in both autosomal dominant and autosomal recessive HL (DFNA8/12 and DFNB21). [71][72][73][74] All presented missense mutations lead to the dominant form, whereas inactivating mutations bring about recessive HL. 75 TECTA mutations have been detected in Austrian, Belgian, French and Swedish families.…”
Section: Tecta Genementioning
confidence: 99%